International Variables Affecting US Foreign Policy Towards North Korea After 2017 - Zaki, Niran Muhammad Ali; Atwan, Khudhir Abbas (Journal of Ecohumanism, 2024)
The international landscape has significantly affected U.S. policy, particularly in the East Asia region. Since 2017, this environment has rapidly evolved, marked by the intensifying Ukrainian crisis, ongoing tensions surrounding Taiwan, and the far-reaching consequences of the COVID-19 pandemic. These developments, along with the impactful rise of President Donald Trump and other pivotal factors, have continuously influenced U.S. policy, especially concerning North Korea. This paper will thoughtfully explore these international dynamics, with specific examples discussed in the following sections.